Predictors of COVID-19 vaccine uptake among adults in South Africa: multimethod evidence from a population-based longitudinal study - Brendan Maughan-Brown; Alison M Buttenheim; Katherine Claire Eyal; Lindokuhle Njozela (BMJ Global Health, 2023)
Background COVID-19 vaccine coverage remains low in many low and middle-income countries despite widespread access. To understand the dynamic decision-making process around vaccination and provide evidence for future vaccine promotion campaigns, we identified predictors of COVID-19 vaccine uptake among South African adults, including those who did not believe in the vaccine’s safety or efficacy.Methods Data from two longitudinal telephone surveys in late 2021 and early 2022 of unvaccinated South African adults were used to model COVID-19 uptake. Predictors of interest informed by the theory of planned behaviour included vaccine attitudes and beliefs, social norms, perceived behavioural control and vaccine intentions. Responses to open-ended questions provided insights into key reasons for getting vaccinated.Results Among panel participants (n=1772), 19% reported being vaccinated between Survey 1 and Survey 2. Vaccine uptake was greater among participants who reported wanting to get vaccinated ‘as soon as possible’ (+27 percentage points, p<0.01). Vaccine uptake was greater among participants who believed that the vaccine is effective in preventing COVID-19 infection and/or death (+12 percentage points, p<0.01) and lower among those who believed that the vaccine is unsafe (−9 percentage points, p<0.01). Among participants who did not believe the vaccine is safe, living with someone already vaccinated against COVID-19 increased vaccine uptake (+6 percentage points, p<0.05). At Survey 1, the intention to get vaccinated as soon as possible was positively associated with perceived risk of illness from COVID-19 (+9.2 percentage points, p<0.05), the belief that most people in their area had been vaccinated (+7.0 percentage points, p<0.05) and living with someone already vaccinated against COVID-19 (+6.6 percentage points, p<0.05).Conclusion Study findings underscore the predictive power of intentions and of beliefs about disease risk, vaccine safety and vaccine efficacy. Social proof interventions hold promise for increasing vaccination intentions and overcoming concerns about vaccine safety.